2007
DOI: 10.1021/la700412m
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hydrophobicity Modulates the Operation of Actomyosin-Based Dynamic Nanodevices

Abstract: We studied the impact of surface hydrophobicity on the motility of actin filaments moving on heavy-meromyosin (HMM)-coated surfaces. Apart from nitrocellulose (NC), which is the current standard for motility assays, all materials tested are good candidates for microfabrication: hydrophilic and hydrophobic glass, poly(methyl methacrylate) (PMMA), poly(tert-butyl methacrylate) (PtBuMA), and a copolymer of O-acryloyl acetophenone oxime with a 4-acryloyloxybenzophenone (AAPO). The most hydrophilic (hydrophilic gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 72 publications
5
27
0
Order By: Relevance
“…The increased sliding velocity for a contact angle up to approximately 80° is broadly consistent with studies by Nicolau et al (2007) who used glass and various polymers for HMM adsorption and found increased velocity with an increase in contact angle up to approximately 70° but a reduction in velocity for higher contact angles. The relationship between velocity and contact angle was however, different in a study (Kolli et al 2010) comparing motility on nitrocellulose (contact angle ~87°), microcontact printed poly(amidoamine) dendrimers (contact angle ~47°) and 3-mercaptopropyl trimethoxysilane (~68°).…”
Section: Developments From 2005 and Onwardssupporting
confidence: 90%
See 2 more Smart Citations
“…The increased sliding velocity for a contact angle up to approximately 80° is broadly consistent with studies by Nicolau et al (2007) who used glass and various polymers for HMM adsorption and found increased velocity with an increase in contact angle up to approximately 70° but a reduction in velocity for higher contact angles. The relationship between velocity and contact angle was however, different in a study (Kolli et al 2010) comparing motility on nitrocellulose (contact angle ~87°), microcontact printed poly(amidoamine) dendrimers (contact angle ~47°) and 3-mercaptopropyl trimethoxysilane (~68°).…”
Section: Developments From 2005 and Onwardssupporting
confidence: 90%
“…Particularly for high contact angles (>70°) the effects on velocity show appreciable variability. Whereas Nicolau et al (2007) found a decrease in velocity for contact angles >70°, Kolli et al (2010) obtained high-quality motility on nitrocellulose with contact angle >80°. In our studies (unpublished) we have observed reduced velocity in occasional experiments with more extensive silanization and a contact angle beyond 80°.…”
Section: Developments From 2005 and Onwardsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the origin of the low velocity of MTs, we performed gliding assay of MTs by changing the substrate and monitored the MTs under HS-AFM. We demonstrated an in vitro gliding assay on collodion (nitrocellulose) coated mica substrate which is a hydrophobic surface 26 (see experimental section). The velocity of MTs was found ~590 nm s −1 on the collodion coated mica substrate, which is very close to the velocity of MTs on glass observed in a conventional gliding assay under fluorescence microscope 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The evolution from single to several globular domains with the increase of the molecular weight of the protein leads to an increase in the roughness of the molecular surface, rather than the change of its overall shape [68]. There are however proteins (not considered here) which exhibit highly elongated shapes, e.g., fibrinogen, but other very large proteins present specialized structures such as coiled coils, e.g., myosin with its very convoluted (and dynamic) shape[69] or the collagen triple helix [67]. Therefore, the difference in the evolution of the decrease of the probed area versus probe radius for proteins with different sizes appears to be the result of either the increased roughness of the molecular surface, or the departure from the globular shape (e.g., for IgG).…”
Section: Resultsmentioning
confidence: 99%